2008
DOI: 10.1364/oe.16.003261
|View full text |Cite
|
Sign up to set email alerts
|

Increased wavelength options in the visible and ultraviolet for Raman lasers operating on dual Raman modes

Abstract: We report increased wavelength options from Raman lasers for Raman media having two Raman modes of similar gain coefficient. For an external-cavity potassium gadolinium tungstate Raman laser pumped at 532 nm, we show that two sets of Stokes orders are generated simultaneously by appropriate orientation of the Raman crystal, and also wavelengths that correspond to sums of the two Raman modes. Up to 14 visible Stokes lines were observed in the wavelength range 555-675 nm. The increase in Stokes wavelengths also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It was in BaWO 4 that stimulated Raman scattering (SRS) with a combined frequency shift of ν 1 + ν 2 was previously observed for the first time [4]. After that, similar effects were studied for many other crystals having a lower Raman gain, including KGd(WO 4 ) 2 , GdVO 4 , YVO 4 , SrWO 4 , SrMoO 4 , Ca 3 (VO 4 ) 2 , PbMoO 4 , and Pb(MoO 4 ) 0.2 (WO 4 ) 0.8 [5][6][7][8][9][10][11]. These effects were experimentally realized in schemes of Raman lasers with a high-Q optical cavity compensating a lower Raman gain at the secondary Raman mode rather than at the primary Raman mode.…”
Section: Introductionmentioning
confidence: 64%
“…It was in BaWO 4 that stimulated Raman scattering (SRS) with a combined frequency shift of ν 1 + ν 2 was previously observed for the first time [4]. After that, similar effects were studied for many other crystals having a lower Raman gain, including KGd(WO 4 ) 2 , GdVO 4 , YVO 4 , SrWO 4 , SrMoO 4 , Ca 3 (VO 4 ) 2 , PbMoO 4 , and Pb(MoO 4 ) 0.2 (WO 4 ) 0.8 [5][6][7][8][9][10][11]. These effects were experimentally realized in schemes of Raman lasers with a high-Q optical cavity compensating a lower Raman gain at the secondary Raman mode rather than at the primary Raman mode.…”
Section: Introductionmentioning
confidence: 64%
“…In the second and more recent study [100], the wavelength options were investigated for a KGW crystal oriented so that the gain is similar for both 768 cm À1 and 901 cm À1 Raman modes. It was shown that it was possible to operate simultaneously on two Raman modes (m 1 and m 2 ) and the Stokes wavelengths oscillating in the resonator consisted of not only the multiple orders of both Stokes lines but also combinations of the two Raman modes.…”
Section: Review Of Experimental Resultsmentioning
confidence: 99%
“…The selection of target wavelengths is also significantly boosted for materials that have more than one active Raman mode [92,100]. Recently, it has been shown that the number of output wavelength choices increases many-fold for Raman materials like KGW, which can be oriented to provide high gain on two Raman modes simultaneously [100].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation